Job satisfaction versus absenteeism in municipalities from Bragança district, Portugal - Ribeiro, Maria Isabel (2021)
In Portuguese public administration, the absenteeism rates were 6.8% in 2017, 4.8% in 2016 and 4.5% in 2015 (INE, 2018). Towards such high absenteeism rates, the Portuguese government has set as priorities, in the 2021 State budget (Ministério das Finanças, 2020), the investment in good working conditions and the control of absenteeism in the Public Administration. So, this research aimed to analyze the association between absenteeism and job satisfaction and to verify if the municipality size is a differentiator factor of both absenteeism and job satisfaction. A cross-sectional and quantitate study was carried out based on a sample of 245 workers from 6 municipalities located in the Bragança district located in the Northeast Portugal. The data were collected using a questionnaire that was administered from April 2018 to July 2019. The data were analyzed using the IBM SPSS Statistics 26.0. In this context, descriptive statistics was used to perform the univariate analysis and Chi-square and R-Pearson tests were used in the bivariate analysis. On average, the number of absences from work was 15.4 days at the medium-sized municipality and 13.2 days at the small-sized municipalities. The level of job satisfaction was a high among municipalities workers. However, the municipality size revealed not to be a differentiator factor of both absenteeism and job satisfaction. Also, no correlation was found between job satisfaction and absenteeism. The main reasons associated with the absence were the need to support the family, natural disease, prolonged illness, demotivation and/or job dissatisfaction, among others.